2021
DOI: 10.1371/journal.pone.0257333
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the menstrual experiences of university students and the impacts on their education: A global perspective

Abstract: Background Higher education attainment is linked to improved health and employment outcomes but the impact of university students’ experiences of menstruation on their education is less clear. The objective of this review was to synthesise qualitative and quantitative research on university students’ menstrual experiences and educational impacts. Methods Eligible studies were identified through systematic searching across eight peer-reviewed databases, websites for menstrual health organisations, grey litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 82 publications
3
60
0
1
Order By: Relevance
“…One of the early studies in 1971 by Kantero and Widholm on over 5,000 female adolescents reported a 43% irregular menstrual cycle rate with 20% having irregular menses 5 years after menarche ( 68 ). Furthermore, studies on non-medical college and school students reported chief complaints of oligomenorrhea or amenorrhea ( 16 , 69 ). These early studies generated a considerable clinical interest to explore further the variability of menstrual patterns and associated symptoms such as PMS, PMDD, and dysmenorrhea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the early studies in 1971 by Kantero and Widholm on over 5,000 female adolescents reported a 43% irregular menstrual cycle rate with 20% having irregular menses 5 years after menarche ( 68 ). Furthermore, studies on non-medical college and school students reported chief complaints of oligomenorrhea or amenorrhea ( 16 , 69 ). These early studies generated a considerable clinical interest to explore further the variability of menstrual patterns and associated symptoms such as PMS, PMDD, and dysmenorrhea.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of menstruation on academics have been studied throughout the century. A recent systematic review established the relationship between dysmenorrhea and academic impairment such as absenteeism, lesser participation in classroom activities, lack of concentration, and degrading academic performance ( 16 ). Female students generally prefer not to seek medical attention or self-medicate using over-the-counter pain killers or other methods to control menstrual pain ( 6 , 10 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…The menstrual cycle is one of the physiological rhythms of life that reflects the health of females. It could be associated with discomfort, pain, anxiety, and changes in the sleep cycle (i.e., peri-menstrual symptoms) and may affect the academic performance in females ( Fernández-Martínez et al, 2020 ; Munro et al, 2021 ). Studies show that systematic yoga practice could have beneficial effects in alleviating such discomfort and symptoms associated with the menstrual cycle in females by stabilizing the neuro-endocrinal axis ( Udupa et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…In line with these findings, a systemic review of the menstrual experiences of university students, and the impact on their education, found that students with more severe menstrual symptoms had greater rates of absenteeism before or at the time of menstruation. 12 …”
Section: Discussionmentioning
confidence: 99%
“…The review found that students’ negative experience of menstruation can negatively impact their education, rate of absenteeism, concentration, interaction and academic participation. 12 …”
Section: Introductionmentioning
confidence: 99%